CREEP BEHAVIOR OF REFRACTORY ALLOYS IN ULTRAHIGH VACUUM. (United States. Dept. of Energy ; distributed by the Office of Scientific and Technical Information, U.S. Dept. of Energy, 1970)
Tungsten Alloys And Systems/hf--re--ta-base--w, Creep Of Astar 811c, Under Vacuum At High Temperature; As-30 (niobium Alloy)/creep In Vacuum At High Temperatures; Tantalum Alloys And Systems/hf--re--ta-base--w, Creep Of Astar 811c, Under Vacuum At High Temperature; T-111 (tantalum Alloy)/creep In Vacuum At High Temperatures; Tzc (molybdenum Alloy)/creep In Vacuum At High Temperatures; Nesdps Office Of Nuclear Energy Space And Defense Power Systems; Cb- 132m (niobium Alloy)/creep In Vacuum At High Temperatures; Tungsten Alloys And Systems/re--w-base, Creep In Vacuum At High Temperature; Rhenium Alloys And Systems/re--w-base, Creep In Vacuum At High Temperature; Tzm (molybdenum Alloy)/creep In Vacuum At High Temperatures; Hafnium Alloys And Systems/hf--re--ta-base--w, Creep Of Astar 811c, Under Vacuum At High Temperature.